3D hierarchical CoFe2O4/CoOOH nanowire arrays on Ni-Sponge for high-performance flexible supercapacitors. (20th April 2020) - Song, Kun; Wang, Xin; Li, Junqing; Zhang, Bin; Yang, Rui; Liu, Peili; Wang, Jun
Abstract: Human activities-enabled mechanical energy as one of the clean energy sources can be stored and used to power electronics. However, there are still lacks of ways to effectively collect and store the human activities-involved mechanical energy. Supercapacitor has been regarded as the most promising solution for this challenge. In this work, CoOOH nanowires were in-situ grown on Ni sponges (NS) with CoFe2 O4 nanolayer by a simple hydrothermal method followed with thermal deposition to prepare supercapacitor electrode. Very interestingly, compared with CoOOH nanowires directly grow on bare NS, the CoOOH nanowires grow on the CoFe2 O4 nanolayers demonstrated more stable microstruture, which interconnected with each other to form a stable three-dimensional scaffold that can ensure sufficient exposure of the active sites to the electrolyte. When used as supercapacitor electrode, the NS/CoFe2 O4 /CoOOH electrode showed ultrahigh specific capacity (200.3 mA h g −1 at 1 mA g −1 ) and excellent cycling stability (92.7% after 2000 cycles at 1 mA g −1 ). The asymmetric electrochemical energy storage device is assembled with NS/CoFe2 O4 /CoOOH as anode and reduced graphene oxide (rGO) polymer composite foam as cathode, which can deliever an energy density of 54.1 W h kg −1 at a power density of 374.9 W kg −1 . Furthermore, a mechanical generator was used to charge the assembled flexible supercapacitor, which demonstrated an average conversion rate of 84% from mechanical energy charging voltage. A fully charged flexible supercapacitor can drive a toy carmore than 5 m, indicating huge potentiol of the assmebled supercapator for mechanical energy storage.